RESEPSI MASYARAKAT PONDOK PESANTREN SUBULUSSALAM SYARIF HIDAYATULLAH PUTRI TERHADAP TRADISI PEMBACAAN SURAT-SURAT PILIHAN - cici noviana noviana; John Supriyanto; Deddy Ilyas (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2021)
This study aims to determine the basis of the arguments for reading selected chapters at the Subulussalam Syarif Hidayatullah Islamic Boarding School for Girls, in order to explain how the implementation procession and the understanding and meaning felt by the perpetors, as well as how the reception of the cottage community towards the tradition of reading these selected chapters. This type of research is field research using the living Qur'an method, so that by going to the field, data and information regarding the implementation of the tradition of reading selected chapters at the Subulussalam Syarif Hidayatullah Islamic Boarding School For Girls are collected clearly and can be responsible for, for data collection methods, namely primary and secondary data sources, using observation methods, interview methods with ethnographic approaches, and documentation methods, while for data analysis techniques in this study using description-explanatory analysis. After conducting a study in this research, it was found that the arguments for the primacy of Yasin's chapters, Al-Waqi'ah and Al-Mulk were the reasons the three chapters were chosen to be used as reading routines for the students. Technically the procession of carrying out the tradition of reading selected chapters begins with reading Surah Al Fatihah as reading hadarah or tawasul to the people who have died, which is then continued by reading selected chapters according to a predetermined schedule, and in the tradition of reading will closed by read the khotmil Qur'an prayer. As for the importance that has been felt by the leaders, administrators and students when they routinely practice the habit of reading these selected chapters from the results of previous interviews with them, namely, as a form of self-approach to Allah SWT, as a form to shape one's personality, and as a form of hope of virtue or fadhilah and blessings from Allah SWT.